CHARACTER BUILDING: THE INSERTION OF LOCAL CULTURE VALUES IN TEACHING AND LEARNING - Darong, Hieronimus Canggung; Jem, Yosefina Helenora; Niman, Erna Mena (UNIVERSITAS PAKUAN, 2021)
This study aims at revealing the values contained in penti ceremony of Manggraian, Flores, NTT the insertion of the values in question in teaching-learning process. Using ethnography approach, data were collected through interview and observation which were subsequently analyzed through some steps namely data reduction, data display and conclusion drawing. The results have shown that penti ceremony has religious, social, and ecological values which can be inserted by means of approach, method and technique of teaching as well as text-books used in teaching-learning process. As one of Indonesian local culture, penti has some values that can be of benefit to build students good character and be a guidance, not only for local people but also for students to properly behave with others and nature.